2005
DOI: 10.1200/jco.2005.01.598
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Inflammation Genes and Bladder Cancer: From Initiation to Recurrence, Progression, and Survival

Abstract: Inflammation gene polymorphisms are associated with modified BC risk, treatment response, and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 28 publications
1
106
1
4
Order By: Relevance
“…94 Recent studies have demonstrated that in bladder tumor cells, which PPARγ expression was weak or absent, standard therapy with Bacillus Calmette-Guerin therapy (BCG), induced cytoplasmic expression of PPARγ. 95 Additionally, it is noteworthy that the inhibition of cell viability by 15-d-PGJ 2 was only detected in the presence of BCG, and the effect of 15-d-PGJ 2 was PPARγ-dependent, since BADGE, a specific PPARγ antagonist, reversed the BCG-mediated cell cytotoxicity.…”
Section: Role In Cancer Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…94 Recent studies have demonstrated that in bladder tumor cells, which PPARγ expression was weak or absent, standard therapy with Bacillus Calmette-Guerin therapy (BCG), induced cytoplasmic expression of PPARγ. 95 Additionally, it is noteworthy that the inhibition of cell viability by 15-d-PGJ 2 was only detected in the presence of BCG, and the effect of 15-d-PGJ 2 was PPARγ-dependent, since BADGE, a specific PPARγ antagonist, reversed the BCG-mediated cell cytotoxicity.…”
Section: Role In Cancer Biologymentioning
confidence: 99%
“…In bladder cancer, polymorphism in genes that regulate inflammatory process such as IL-6 and PPARγ are associated with recurrence risk, progression and survival. 94 Patients with PPARγ variant alleles (Single Nucleotide Polymorphism-Pro12Ala) show decreased PPARγ receptor activity and are associated with an increased risk of bladder cancer recurrence and progression. 94 The Our previous work had shown that modulation of glycogen synthase kinase-3 beta (GSK-3β) and cyclin D1 might be a predictor of response to EGFR inhibitors in bladder cancer.…”
Section: Pparγ and Pparγ-agonists In Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The TNF-α 308G/A polymorphism is a G/A polymorphism at nucleotide (nt) -308, and is associated with the development of several urogenital cancers, including prostate cancer (Zabaleta et al, 2008;Moore et al, 2009;Jones et al, 2013), cervical cancer (Singh, 2009;Zuo et al, 2011), bladder cancer (Jeong et al, 2004;Kim et al, 2005;Leibovici et al, 2005), and renal cell carcinoma (Jang et al, 2001). For example, Jeong et al (2004) studied 113 patients with bladder cancer and 109 healthy subjects and found that the genotype of the 308 nucleotide in the TNF-α promoter had a statistically significant effect on TNF-α production and was related to the bladder tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…There are 13 studies (Oh et al, 2000;McCarron et al, 2002;Wu, 2004;Jinchao, 2007;Danforth et al, 2008;Sáenz-López et al, 2008;Zabaleta et al, 2008;Kesarwani, 2009;Moore et al, 2009;Wang et al, 2009a;Zhang et al, 2010;Berhane et al, 2012;Jones et al, 2013) focusing on prostate cancer, 19 studies (Jang et al, 2001;Calhoun et al, 2002;Gostout et al, 2003;Stanczuk et al, 2003;Deshpande et al, 2005;Duarte et al, 2005;Govan, 2006;Kohaar et al, 2007;Singh, 2009;Wang et al, 2009b;Ivansson, 2010;Zu, 2010;Wang et al, 2011;Zuo et al, 2011;Badano et al, 2012;Barbisan et al, 2012;Hang and Xu, 2012;Wang et al, 2012;Sousa et al, 2014) on cervical cancer, 6 studies (Tsai et al, 2001;Jeong et al, 2004;Kim et al, 2005;Leibovici et al, 2005;Nonomura et al, 2006;Ahirwar et al, 2008) on bladder cancer, 1 study (Jang et al, 2001) on renal cell cancer, and 1 study (Wu, 2013) on urothelial carcinoma. Five articles (Stanczuk et al, 2003;…”
Section: Study Characteristicsmentioning
confidence: 99%